Pengaruh Investasi, Jumlah Penduduk, dan Inflasi Terhadap Produk Domestik Regional Bruto di Provinsi Jawa Tengah Periode 2014-2018 - Teges Widiyarto (Diponegoro Journal of Economics, 2022)
Gross Regional Domestic Product is a variable to see developments in Central Java Province, which is a province that has the potential for a high level of economic growth. Investment plays an important role as a driving factor for economic growth, both investment in the form of fixed capital and human capital. In addition, the population as an economic actor plays an important role. Inflation plays an important role is there any effect of high inflation on GRDP. This study aims to analyze the effect of investment, population, and inflation on Gross Regional Domestic Product in Central Java Province in 2014-2018. The research data used is the value of the Regional Gross Domestic Product (GRDP), the Gross Fixed Capital Formation (PMTB), the total population, and inflation. The data was processed by regression analysis of the Eviews12 panel data using the Random Effect Model (REM) approach. The results of the study show that increasing investment from year to year will significantly increase the GRDP in Central Java Province. increasing population increases the GRDP of Central Java Province significantly, stable inflation has not significantly affected the GRDP of Central Java Province.